1997
DOI: 10.1073/pnas.94.21.11439
|View full text |Cite
|
Sign up to set email alerts
|

The role of Wolbachia bacteria in reproductive incompatibilities and hybrid zones of Diabrotica beetles and Gryllus  crickets

Abstract: A rickettsial bacterium in the genus Wolbachia is the cause of a unidirectional reproductive incompatibility observed between two major beetle pests of maize, the western corn rootworm, Diabrotica virgifera virgifera, and the Mexican corn rootworm, D. v. zeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
3
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 38 publications
5
88
3
1
Order By: Relevance
“…Only recently, though, have Wolbachia been implicated in the one-way cross incompatibility between G. pennsylvanicus males and G. Þrmus females. This suggestion was made by Giordano et al (1997), who found that G. pennsylvanicus was infected with Wolbachia, while G. Þrmus was not. Thus, the one-way incompatibility could seemingly be explained by Wolbachia-induced unidirectional CI (Giordano et al, 1997).…”
Section: Model 2 (Ci Coupled With Genetically Based Isolation)mentioning
confidence: 93%
See 2 more Smart Citations
“…Only recently, though, have Wolbachia been implicated in the one-way cross incompatibility between G. pennsylvanicus males and G. Þrmus females. This suggestion was made by Giordano et al (1997), who found that G. pennsylvanicus was infected with Wolbachia, while G. Þrmus was not. Thus, the one-way incompatibility could seemingly be explained by Wolbachia-induced unidirectional CI (Giordano et al, 1997).…”
Section: Model 2 (Ci Coupled With Genetically Based Isolation)mentioning
confidence: 93%
“…This suggestion was made by Giordano et al (1997), who found that G. pennsylvanicus was infected with Wolbachia, while G. Þrmus was not. Thus, the one-way incompatibility could seemingly be explained by Wolbachia-induced unidirectional CI (Giordano et al, 1997). However, a more recent study of infection patterns and species identity by Mandel et al (2001) has disputed this conclusion.…”
Section: Model 2 (Ci Coupled With Genetically Based Isolation)mentioning
confidence: 93%
See 1 more Smart Citation
“…The bacteria can alter the reproductive biology of their hosts in several ways, like uni or bidirectional incompatibility, sex ratio biases, parthenogenesis and host fecundity (reviews in Werren and Guo, 1995a;Johanowicz and Hoy, 1998). Wolbachia-like organisms may also cause reproductive isolation of different geographical strains of Drosophila species (Boyle et al, 1993), and may be one mechanism involved in speciation processes (Werren, 1997;Giordano et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An alignment (984 positions, counting the insertions^deletions, indels), including the ftsZ DNA sequences obtained from ¢larial wolbachiae and those reported in Werren et al (1995) and in Giordano et al (1997), was then constructed according to the scheme in Werren et al (1995). For some analyses, A. marginale was included as an outgroup.…”
Section: (B) Data Analysismentioning
confidence: 99%